2019
DOI: 10.3389/fncel.2019.00285
|View full text |Cite
|
Sign up to set email alerts
|

Advances and Challenges in Pharmaceutical Therapies to Prevent and Repair Cochlear Injuries From Noise

Abstract: Noise induces a broad spectrum of pathological injuries to the cochlea, reflecting both mechanical damage to the delicate architecture of the structures of the organ of Corti and metabolic damage within the organ of Corti and lateral wall tissues. Unlike ototoxic medications, the blood-labyrinth barrier does not offer protection against noise injury. The blood-labyrinth barrier is a target of noise injury, and can be weakened as part of the metabolic pathologies in the cochlea. However, it also offers a potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 125 publications
(213 reference statements)
0
8
0
Order By: Relevance
“…A number of pharmacologic interventions to help protect the ear from over-exposure to loud noise appear to be on the horizon, but nothing is FDA-approved yet [ 248 , 249 ]. Hearing aids are helpful but do not restore natural hearing ability, and there is currently no cure for tinnitus or hyperacusis [ 250 ], nor for bringing back lost cochlear hair cells and nerve fibers [ 251 , 252 , 253 ]. NIHL can precipitate depression, social withdrawal, and cognitive decline [ 254 , 255 , 256 , 257 , 258 , 259 , 260 ], and mild, moderate, and severe hearing loss increases the risk of dementia by 2-, 3- and 5-fold, respectively [ 261 , 262 , 263 ].…”
Section: Preventing Noise-induced Hearing Lossmentioning
confidence: 99%
“…A number of pharmacologic interventions to help protect the ear from over-exposure to loud noise appear to be on the horizon, but nothing is FDA-approved yet [ 248 , 249 ]. Hearing aids are helpful but do not restore natural hearing ability, and there is currently no cure for tinnitus or hyperacusis [ 250 ], nor for bringing back lost cochlear hair cells and nerve fibers [ 251 , 252 , 253 ]. NIHL can precipitate depression, social withdrawal, and cognitive decline [ 254 , 255 , 256 , 257 , 258 , 259 , 260 ], and mild, moderate, and severe hearing loss increases the risk of dementia by 2-, 3- and 5-fold, respectively [ 261 , 262 , 263 ].…”
Section: Preventing Noise-induced Hearing Lossmentioning
confidence: 99%
“…Although the cochlea may be described as a dynamic and immunogenic environment that is susceptible to a wide array of immune insults and pathogens, it was long considered as “immune privileged” due to the presence of tight junctions within the blood-labyrinth barrier (BLB), which prevent entry and establishment of immune cells in the cochlea [ 105 ]. Entry of cells into the inner ear by the BLB has also heavily restricted advancement of drug and cell-based therapies for cochlea treatment [ 106 , 107 ]. Perhaps because of this barrier, much work to date on defining the pathology of SNHL has focused on the cochlear architecture, including mechanosensory hair cells, the stria vascularis, the spiral ganglion, or cochlear synapse connectivity [ 67 , 102 ].…”
Section: The Cochlea As a Model Organ To Study The Effect Of Early Life Inflammation On The Developing Hematopoietic And Immune Systemsmentioning
confidence: 99%
“…Microspheres (diameters in the range of 1 ÎĽm) can pass through the RWM of the rabbit ( Goycoolea et al, 1988 ), and nanoparticles with diameters in the range of 170–190 nm can pass through the RWM of the rat ( MartĂ­n- Saldaña et al, 2018 ). Additionally, literature indicated that noise exposure can induce alterations to the BLB, which can make it easier for drugs to reach the organ of Corti ( Suzuki et al, 2002 ; Wu et al, 2014 ; Bielefeld and Kobel, 2019 ). Our results also demonstrated that SOD@ZIF-8 nanoparticles can cross the RWM and BLB following their administration.…”
Section: Resultsmentioning
confidence: 99%